Effect of Comprehensive Complementary Feeding Intervention on Maternal Self-Efficacy in Feeding Infants Aged 6–12 Months - Ayu Rahmadani; Ari Nofitasari; Islaeli Islaeli (Waluya The International Science of Health Journal, 2026)
Introduction: Stunting remains a chronic nutritional problem in Indonesia, including in Southeast Sulawesi and Kendari City, particularly in coastal areas such as Kendari, Abeli, and West Kendari Districts. One of the main causes of stunting is inappropriate provision of complementary foods in terms of timing, quality, and quantity. Many mothers provide Complementary Foods for Breast Milk too early, lack variety, and rely on instant foods. Low maternal self-efficacy also influences Complementary Foods for Breast Milk provision practices. This study aims to Effect of Comprehensive Complementary Feeding Intervention on Maternal Self-Efficacy in Feeding Infants Aged 6–12 Months. Method: The study used a quasi-experimental design with a pre-test, post-test, and control group design. It was conducted in May–June 2025 in the Abeli, Mata, and Benu-Benua Community Health Centers. The sample consisted of 67 infants aged 6–12 months selected using stratified random sampling. Data were collected through questionnaires, interviews (with 2x24-hour recall), and weight measurements. Result: The data were not normally distributed (Kolmogorov Smirnov test), but there was a significant effect of comprehensive complementary feeding intervention on self-efficacy (p < value = 0.000). Conclusion: Mothers of toddlers are expected to increase their self-confidence and provide a variety of foods daily. Community health centers need to provide comprehensive, practical complementary feeding education and training, and future researchers are encouraged to examine other factors, such as psychosocial and environmental aspects.